2002
DOI: 10.1046/j.1475-097x.2002.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle mitochondrial ATP production rate and walking performance in peripheral arterial disease

Abstract: This study tested the hypotheses that skeletal muscle mitochondrial ATP production rate (MAPR) is impaired in patients with peripheral arterial disease (PAD) and that it relates positively to their walking performances. Seven untrained patients, eight exercise-trained patients and 11 healthy controls completed a maximal walking test and had muscle sampled from the gastrocnemius medialis muscle. Muscle was analysed for its MAPR in the presence of pyruvate, palmitoyl-L-carnitine or both, as well as citrate synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 34 publications
5
44
1
3
Order By: Relevance
“…The observation that PPO was lower in the IC patients than the controls is consistent with the limited muscular strength and endurance capacities of IC patients previously described (13,35), and the well-established reduction in their tolerance for physical activities such as walking and cycling (2,28). Several studies have investigated the mechanisms of exercise intolerance in IC patients.…”
Section: Discussionsupporting
confidence: 85%
“…The observation that PPO was lower in the IC patients than the controls is consistent with the limited muscular strength and endurance capacities of IC patients previously described (13,35), and the well-established reduction in their tolerance for physical activities such as walking and cycling (2,28). Several studies have investigated the mechanisms of exercise intolerance in IC patients.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have shown that exercise tolerance is severely impaired in patients with claudication and that, on average, maximum exercise times are ∼40 to 50% of those values observed in healthy controls [1][2][3][4]. These data are based on studies that have excluded individuals with type 2 diabetes, yet a significant number of patients with claudication have type 2 diabetes (see Introduction).…”
Section: Discussionmentioning
confidence: 99%
“…walking performance) by claudicants is $ 50% or less than that observed in healthy controls. 10,32,37,51 Within a group of claudicants there is a large range of performances on a graded treadmill test, where the upper limit can overlap with the lower limit of healthy controls (Figure 2; x axis 10 ). Many factors could contribute to this large variation in walking performance amongst claudicants, 52 including aerobic and mitochondrial metabolism.…”
Section: Walking Performance and Metabolismmentioning
confidence: 99%